Association between Stress Levels, Sleep Quality, and Menstrual Cycle among Female Adolescents - Mia Audina; Nova Mardiana (Genius Journal, 2026)
Objective: Menstruation is bleeding caused by the shedding of the inner lining of the uterus, known as the endometrium. Menstrual bleeding occurs regularly, and the time interval between one menstruation and the next is referred to as one menstrual cycle. Menstrual disorders can be caused by several factors, including stress and sleep quality. The level of stress experienced can affect the length of the menstrual cycle because perceived stress triggers the release of cortisol, a hormone that regulates various body systems. Meanwhile, poor sleep quality can inhibit the production of melatonin, a hormone that also influences the menstrual cycle. This study aimed to determine the relationship between stress level and sleep quality with the menstrual cycle among female adolescents at SMAN 1 Belinyu in 2025.. Method: This study employed a cross-sectional design. The population consisted of 147 female students at SMAN 1 Belinyu, with a sample size of 66 respondents. The research was conducted on November 24, 2025, at SMAN 1 Belinyu. Result: The results of the study using the chi-square test showed that stress level obtained a p-value of 0.000 < α (0.05), and sleep quality also obtained a p-value of 0.000 < α (0.05). These results indicate that there is a significant relationship between stress level and sleep quality with the menstrual cycle among female adolescents at SMAN 1 Belinyu in 2025. Conclusion: The conclusion of this study is that there is a relationship between stress level and sleep quality with the menstrual cycle among female adolescents at SMAN 1 Belinyu in 2025. The recommendation of this study is that it is expected to serve as a reference for schools to collaborate with health centers in providing educational materials on stress management and maintaining good sleep quality in order to prevent irregular menstrual cycles